Ontological aspects in the formalisation of the FrameNet inheritance relationship. (2015) - Moreira, Alexandra; Oliveira, Alcione De Paiva; Salomão, Maria Margarida M.; Cerqueira, Fábio Ribeiro
FrameNet is a lexical semantic resource consisting of a set of frames related by semantic links. It is a rich network of concepts and relationships. However, from the point of view of some researches, it has some limitations such as the lack of formalisation. In this paper, we propose to formalise the elements of FrameNet and the inheritance relationship, based on ontological principles in order to facilitate its use in inferences. Furthermore, it is expected that the formalisation of the FrameNet elements solves problems related to ambiguities. In this case, rules were formulated in formal language and were applied to natural language sentences in order to assess their degree of membership to a particular scene. The results showed that this approach can help produce better defined frames.